Effects of Irritability of the Youth on Subjective Well-Being: Mediating Effect of Coping Styles - Ling ZHANG; Benxian YAO; Xiaodan ZHANG; Hao XU (Tehran University of Medical Sciences, 2020)
Background: The global COVID-19 pandemic caused great impacts and influences to human psychology. As a result, youths who are kept at home for a long time easily develop irritability and problematic behaviors. However, relatively little attention has been paid to the relations among irritability, coping style, and subjective well-being of the youth. Methods: Overall, 1,033 youth respondents (aged 18-30 yr) from seven provinces in China were investigated in 2020 using the irritability, depression, and anxiety scale, coping style scale, and well-being index scale. Results: Among the dimensions of irritability of the youth, anxiety received the highest score, followed by introversion irritability, extroversion irritability, and depression. Irritability had significant regional differences. The total score of irritability among rural youth was significantly higher than that of urban youth (P<0.05). The irritability level of youths with parents' emotional status was harmonious and good relations with family members and peers was far lower than those of youths who have poor relations between parents, family members, and peers (P<0.05). The irritability level of youths with a lower monthly household income was higher (P<0.05). Irritability of the youth had significantly negative correlations with positive response and SWB, and it had a significantly positive correlative with negative response. Coping style can mediate the relationship between irritability and SWB of the youth to some extent. Conclusion: Significant correlations exist among irritability, coping style, and SWB of the youth. Irritability can be used to predict SWB indirectly through positive response.